Design of Dual Purpose Fe‐metallogel for Magnetic Refrigeration and Fabrication of Schottky Barrier Diode. Issue 41 (2nd November 2022) - Saha, Sayan; Pal, Baisakhi; Sundar Das, Krishna; Kumar Ghose, Pradeepta; Ghosh, Avik; De, Avik; Kumar Das, Abhijit; Pratim Ray, Partha; Mondal, Raju
Abstract: The impetus for the present work was to design multifunctional inorganic materials that can be utilized in their original as‐synthesized state of the matter. Accordingly, we have successfully designed a benzene‐tricarboxylic acid based dual‐purpose Fe‐metallogel that can be used as an efficient material for cryogenic magnetic cooling as well as electronic device fabrication as Schottky barrier diode in their original gel state. The metallogel shows remarkable mechanical strength, self‐sustainability and thixotropic behaviour. The gel sample has been thoroughly characterized using IR, UV‐Vis spectroscopy, SEM, TEM, AFM techniques, XPS and Mössbauer spectroscopy. The porous nature, which forms the basis of the current gel based MCE study and SBD fabrication, was confirmed with gas sorption data. The porous metallogel network with by‐default entrapped anion and protic solvents of the fabricated electrical device provides an excellent platform for charge transportation with a corroborating conductivity value of 4.53×10 −6 Sm −1 . As if to complement the notion of multifunctional material, the magnetic studies on the Fe‐gel show significant cryogenic magnetic cooling behaviour. The theoretical result calculated using DFT are found to be highly consistent with the experimental results of the metallogel. Furthermore, we have evaluated the potential of the compound as a fuel cell membrane with detailed proton conductivity measurements on the xerogel, showing an encouraging value of 4.58×10 −4 S/cmat 95 % relative humidity and 75 °C temperature. Abstract : The Fe‐1, 2, 4‐benzenetricarboxylic acid metallogel shows remarkable mechanical strength, self‐sustainability and thixotropic behaviour. The gel sample has been thoroughly characterized using IR, UV‐Vis spectroscopy, SEM, TEM, AFM techniques, XPS and Mössbauer spectroscopy. The porous nature, which forms the basis of the current gel‐based MCE study, Proton conductivity study& SBD fabrication, was confirmed with gas sorption data. The porous metallogel network with by‐default entrapped anion and protic solvents of the fabricated electrical device provides an excellent platform for charge transportation with a corroborating conductivity value of 4.53×10 −6 Sm −1 and proton conductivity gives the value of 4.58×10 −4 & the value of Magneto Caloric Effect is 1.58 J Kg −1 K −1 .